Esophageal spirocercosis with pulmonary egg deposition and secondary hypertrophic osteopathy in a dog from Costa Rica - De Aguiar, Ivana (2021)
Spirocerca lupi is the etiologic agent of spirocercosis in canids from the tropical and subtropical regions of the world. A 1-year-old dog was presented with weight loss and diarrhea. Upon examination, thickened limbs, a mass in the lung’s right middle lobe and an esophageal mass were found. The pulmonary mass aspirate revealed S. lupi eggs surrounded by a purulent infiltrate. Limb bone biopsies showed irregular mineralization and cartilaginous metaplasia. Treatment with doramectin resolved the initial clinical signs. However, regurgitation was reported 5 months later. Therefore, the dog received additional doramectin and later vomited a worm morphologically consistent with a S. lupi adult. Herein we report the esophageal migration of S. lupi with egg deposition to the lung parenchyma, accompanied by secondary hypertrophic osteopathy. This report highlights the presence of S. lupi in Costa Rica and the importance of including this parasite as a differential diagnosis when compatible signs are identified.